Kajian Kualitas Air dan Penentuan Status Mutu Air Sungai Cakung, Kota Jakarta - Annisa Indriany; Dwi Nowo Martono; Haruki Agustina (Universitas Riau, 2024)
The Cakung River is a river located east of Jakarta and empties directly into the Cilincing estuary, on the coast of DKI Jakarta. The Cakung River crosses a densely populated area and becomes a waste disposal site for various types of industries, resulting in a decline in river water quality. The decline in the quality of the Cakung River will affect Jakarta’s coastal area which has a strategic ecological function. This study aims to analyze the water quality and water quality status of the Cakung River using the pollution index method. The results were also compared with measurements in 2021 and 2019. Laboratory analysis showed that the main pollutant parameters such as TSS, BOD, COD, and Faecal coliform exceeded the quality standards at all sampling points. The range of TSS values was 42-3450 mg/L, BOD 11.1-23.64 mg/L, COD 30-100 mg/L, Faecal coliform 5x106-9x106 MPN/100 mL. The pollution index calculation results show that the Cakung River is severely polluted with index value ranging from 13.92-14.86 and the level of severe pollution has also been going on since 2019. Therefore, serious efforts to control pollution in the Cakung River are needed.